Developing Pop-Up Book to Teach Vocabulary - Yusroh Yusroh (Language-Edu, 2020)
This Research and Development was a research conducted developing pop-up book to teach vocabulary for first grade of SMPN 2 Wagir Malang. It applied R&D cycles which were presented by Borg and Gall (1979). The steps were: (1) need analysis, (2) material development, (3) product development, (4) expert validation, (5) product revision (6) try out, (7) field test, and (8) final product. Its sources of data were the students, English teacher, and pop-up book. Its instruments were interview guide, questionnaire and observation notes. The product was developed based on the result of the need analysis. Then, the try out was held in order to know students respond of the product. After doing the try out the researcher conducted the field test. The expert argued that the pop-up book included a good pop-up book and the expert gave some suggestions to revise the pop-up book. The pop-up book was tried out to know its acceptability. The result of try out was the pop-up book was good and attractive but the pop-up book needs more variation in term of the type of the picture, exercise and more challenging topic and the object need more pictures and sentences. The result of the field test was pop-up book was acceptable and no need revision. It was hoped that this pop-up book can be used to be sources of media in teaching English especially to teach vocabulary.